Pengaruh Pemupukan Berimbang Spesifik terhadap Pertumbuhan Tanaman Gaharu (Gyrinops versteegii) dan Perubahan Beberapa Sifat Kimia Tanah - A.A. NYOMAN SUPADMA; I MADE DANA; I MADE MEGA (Agrotrop : Journal on Agriculture Science, 2018)
Effect of Fertilizer (Organic + Inorganic + Dolomite) Combination to Improve of Growth Gaharu Plant (Gyrinops versteegii) and Characteristic of Soil Chemistry. This study aims to find combinations of fertilizer (organic + inorganic + dolomite) to promote the growth of gaharu plant and chemical properties of soil. This research was conducted in Tabanan Regency. The study was a randomized block design (RBD) with 7 treatments, each treatment was repeated three times to obtain 21 gaharu plants as a crop sample. The fertilizer formulations were tested as treatments as follows: A = without fertilizer (control), B = (50 g urea + 50 kg SP-36 + 50 kg KCl + 10 kg compost) + 50 g Dolomite) per tree, C = (100 g urea + 100 g SP-36 +100 g KCl + 7.5 kg compost + 75 g Dolomite) per tree, D = (150 g urea +150 g SP-36 + 150 g KCl + 5 kg compost + 75 g Dolomite) per tree, E = (200 g urea + 200 g SP-36 + 200 g KCl + 2.5 kg of compost + 100 g Dolomite) per tree, F = (200 g urea + 150 g SP -36 + 150 g KCl + 7.5 kg of compost + 100 g Dolomite) per tree, G = (200 g urea + 100 g SP-36 + 100 g KCl + 7.5 kg of compost + 75 g Dolomite) per tree. Parameters measured were plant height, girth of plants, and chemical properties of the soil. Analysis of data using analysis of variance and Duncan test (0.05). The results showed that fertilization treatments significantly affected plant height, but not significant to girth of plant. The best fertilizer combinations was the treatment of C, which were increase plant height (26,35 cm), pH (6,7), total N (0,28 %) and other chemical properties of soil.